2020
DOI: 10.3390/cancers12113303
|View full text |Cite
|
Sign up to set email alerts
|

The Organoid Era Permits the Development of New Applications to Study Glioblastoma

Abstract: Glioblastoma (GB) is the most frequent and aggressive type of glioma. The lack of reliable GB models, together with its considerable clinical heterogeneity, has impaired a comprehensive investigation of the mechanisms that lead to tumorigenesis, cancer progression, and response to treatments. Recently, 3D cultures have opened the possibility to overcome these challenges and cerebral organoids are emerging as a leading-edge tool in GB research. The opportunity to easily engineer brain organoids via gene editing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 111 publications
(141 reference statements)
0
13
0
1
Order By: Relevance
“…The specimens of excision established Application of Ex-Vivo/3D Organoid Models in COVID-19 Research DOI: http://dx.doi.org/10.5772/intechopen.99100 by these transitory bronchus explant cultures. Hui et al [10] the expected replication capacity, tropism in the tissue and the generation of cytokines inducing bronchi-and human-aviation pathways organoids from human and avian strains of flu. These tests provide appropriate findings by using organoids and explants.…”
Section: D Organoids and Virologymentioning
confidence: 99%
See 1 more Smart Citation
“…The specimens of excision established Application of Ex-Vivo/3D Organoid Models in COVID-19 Research DOI: http://dx.doi.org/10.5772/intechopen.99100 by these transitory bronchus explant cultures. Hui et al [10] the expected replication capacity, tropism in the tissue and the generation of cytokines inducing bronchi-and human-aviation pathways organoids from human and avian strains of flu. These tests provide appropriate findings by using organoids and explants.…”
Section: D Organoids and Virologymentioning
confidence: 99%
“…Multiple organs are joined to generate the spinal tract, which arises from a rudimentary general tube that is elaborated between the mouth and the anus. The gut tube [10] has endodermal layer pillage, which has a three-region subdivision. Hindgut, midgut and Foreskin, where each location in the development of the embryonal layer produces certain organs throughout specific intervals.…”
Section: Gut Organoidsmentioning
confidence: 99%
“…At the same time, in the in vitro model, the cerebral organoids derived from human tissue have the advantage of imitating the interaction between in vivo structure and environment, and have more reliable clinical significance compared with the mouse derived model. With these factors in mind, gene editing in human brain organoids has made it possible to study the early stages of tumorigenesis and cancer progression [ 57 ].…”
Section: Cerebral Organoids As a Model For Gliomamentioning
confidence: 99%
“…Their use as patient avatars in personalized therapy drug screens [ 111 ] has demonstrated that organoids are able to model and predict patient responses. In particular, the derivation of organoids from patient tumors (patient-derived organoids or PDOs) or iPSCs in colorectal [ 112 , 113 ], breast [ 114 , 115 , 116 ], liver [ 117 , 118 , 119 , 120 ], pancreatic [ 121 , 122 , 123 , 124 ] and neurological cancers [ 125 , 126 , 127 , 128 , 129 , 130 ] have collectively demonstrated the scalability of organoids in vitro, their ability to recapitulate tumor phenotypes and maintain genetic backgrounds and offer significant prognostic value of various therapeutic interventions. The further incorporation of immune cells in co-culture with PDOs would greatly improve physiological significance and prognostic impact of functional drug screens, especially in the context of immune checkpoint blockades [ 131 ].…”
Section: Overview Of Current Experimental Models In Cancermentioning
confidence: 99%